2012
DOI: 10.1111/j.1600-0501.2012.02544.x
|View full text |Cite
|
Sign up to set email alerts
|

What is the optimal number of implants for removable reconstructions? A systematic review on implant‐supported overdentures

Abstract: For the maxilla there are no studies, at the present time, that can be utilized to address the question of how many implants should support an overdenture. For the mandible, it cannot be concluded that bone loss, patient satisfaction, or number of complications is significantly related to the number of implants supporting the overdenture. Furthermore, splinting two implants does not seem to offer additional value. Well conducted research is needed to identify the prognostic factors for long-term success.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
78
0
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(85 citation statements)
references
References 41 publications
1
78
0
6
Order By: Relevance
“…The results improved when maxillary implant overdentures were made as a planned treatment following strict protocols 13. Nevertheless it is evident that maxillary implant overdentures present a number of different challenges compared to the predictable benefits of mandibular 2-implant overdentures 46,47. Systematic reviews concluded that maxillary overdentures on 4 or more implants in a splinted construction provided high survival (> 95% for the first year) both for implants and overdenture 14,48.…”
Section: Maxilary Implant Overdenturementioning
confidence: 99%
“…The results improved when maxillary implant overdentures were made as a planned treatment following strict protocols 13. Nevertheless it is evident that maxillary implant overdentures present a number of different challenges compared to the predictable benefits of mandibular 2-implant overdentures 46,47. Systematic reviews concluded that maxillary overdentures on 4 or more implants in a splinted construction provided high survival (> 95% for the first year) both for implants and overdenture 14,48.…”
Section: Maxilary Implant Overdenturementioning
confidence: 99%
“…21 Mevcut literatür bilgileri dahilinde üst çene için iyi planlanmış uzun dönemli çalışma-lara ihtiyaç duyulmaktadır. 13 Yüksek maliyet, inter okluzal mesafenin fazla olma gerekliliği, yapım ve tamirinin zor olması, bu tutucu tipinin kullanımını kısıtlayan faktörler arasındadır.…”
Section: Bar Tutucularunclassified
“…Most complaints are related to retention and stability of dentures especially in mandibles. For these patients implant-supported overdentures can be an effective treatment (1)(2)(3). Implant-supported overdentures compared with complete dentures have more retention and stability and have less cost than complete implant-supported fixed prosthesis, and even years after, more implants can be added to the treatment plan.…”
Section: Introductionmentioning
confidence: 99%